1986
DOI: 10.1007/bf00938793
|View full text |Cite
|
Sign up to set email alerts
|

Screening of white-rot fungi for biological pretreatment of wheat straw for biogas production

Abstract: Summary. Twenty two basidiomycetes, mostly white rot fungi, were grown on wheat straw. Lignin-, cellulose-, and hemicellulose-degradation was recorded in order to find a species growing on lignin preferably. The "oyster-mushroom" Pleurotus sp. "florida'" showed fastest delignification of all tested fungi.Straw pretreated by this fungus was fermented anaerobically to biogas. The gas yield produced from "myco-straw" is twice the amount from untreated straw.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Higher biogas yield of pretreated corn stover was not achieved. Some other lignocellulosic biomass like wheat straw [98][99][100] , Japanese cedar wood 101 , and rice straw 102,103 , have also been successfully degraded using whiterot fungi, which ultimately affected the increase in the production of biogas.…”
Section: Biological Pretreatmentmentioning
confidence: 99%
“…Higher biogas yield of pretreated corn stover was not achieved. Some other lignocellulosic biomass like wheat straw [98][99][100] , Japanese cedar wood 101 , and rice straw 102,103 , have also been successfully degraded using whiterot fungi, which ultimately affected the increase in the production of biogas.…”
Section: Biological Pretreatmentmentioning
confidence: 99%
“…Moreover, fungi with high lignin-degrad- ing selectivity and/or degradation ability are preferred. Fungi with high lignin-degrading selectivity have been proved to enhance methane production from lignocellulosic biomass [5,7,9]. Fungi with high degradation ability decay lignocellulosic biomass rapidly and throughly to enhance yeast production for improvement of protein content and palatability of feed [2].…”
Section: Discussionmentioning
confidence: 99%
“…has shown high lignin-degrading selectivity in different types of lignocellulosic biomass decayed and has been used to enhance methane production [9,24]. �üller and Trösch [9] concluded that Pleurotus florida showed the fastest delignification among twenty-two tested fungi. Wheat straw pretreated by this fungus was fermented anaerobically to biogas, and the gas yield was twice the amount of the untreated straw.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subtrates with high content of cellulose and lignin that interlink each other [10], becomes difficult to hydrolyze, so that the yield of biogas is low. To overcome this, some researchers have proposed some pretreatment processes before processing in AD, such as thermo-chemical [12], thermal [2,1], mechanical-chemical-enzymatic [3], alkaline [7], and biological [9] pretreatments. The methods are successful for enhancing the yield of biogas, but the pretreatment processes are less practical, as they require additional equipment and also sometimes use additional chemicals that may add an operational cost.…”
Section: Introductionmentioning
confidence: 99%